A Guide to Carrying Out a Phylogenomic Target Sequence Capture Project - Andermann, Tobias; Torres Jiménez, Maria Fernanda; Matos-Maraví, Pável; Batista, Romina; Blanco-Pastor, José L.; Gustafsson, A. Lovisa S.; Kistler, Logan; Liberal, Isabel M.; Oxelman, Bengt; Bacon, Christine D.; Antonelli, Alexandre (Frontiers in Genetics, 2020)
High-throughput DNA sequencing techniques enable time- and cost-effective sequencing of large portions of the genome. Instead of sequencing and annotating whole genomes, many phylogenetic studies focus sequencing efforts on large sets of pre-selected loci, which further reduces costs and bioinformatic challenges while increasing sequencing depth. One common approach that enriches loci before sequencing is often referred to as target sequence capture. This technique has been shown to be applicable to phylogenetic studies of greatly varying evolutionary depth and has proven to produce powerful, large multi-locus DNA sequence datasets of selected loci, suitable for phylogenetic analyses. However, target capture requires careful theoretical and practical considerations, which will greatly affect the success of the experiment. Here we provide an easy-to-follow flowchart for adequately designing phylogenomic target capture experiments, and we discuss necessary considerations and decisions from the first steps in the lab to the final bioinformatic processing of the sequence data. We particularly discuss issues and challenges related to the taxonomic scope, sample quality, and available genomic resources of target capture projects and how these issues affect all steps from bait design to the bioinformatic processing of the data. Altogether this review outlines a roadmap for future target capture experiments and is intended to assist researchers with making informed decisions for designing and carrying out successful phylogenetic target capture studies.